Penanganan Flare-Up Pasca Obturasi pada Perawatan Saluran Akar Jamak: Laporan Kasus - Cahyani, Cahyani; Kirom, Fiqi F. (Universitas Sam Ratulangi, 2026)
Abstract: Post-obturation flare-up is an endodontic complication characterized by acute pain resulting from inflammatory responses in periapical tissues. Contributing factors include debris extrusion, inadequate obturation, and sealer toxicity. We reported an 18-year-old male presented with pain in the upper left maxillary premolar three days after root canal obturation. Radiographic and CBCT evaluation revealed underfilling of the palatal root canal. Retreatment was performed by removing gutta-percha with an H-file and orange oil, followed by re-preparation using the crown-down technique. Irrigation was carried out with 2.5% NaOCl and 2% chlorhexidine. Intracanal medication with a mixture of calcium hydroxide and 2% chlorhexidine paste was applied. After one week, the patient was asymptomatic, and re-obturation was completed using the lateral condensation technique with eugenol-based sealer. In the two-week follow-up, the patient remained symptom-free, and definitive restoration with a porcelain-fused-to-metal crown was placed. In conclusion, post-obturation flare-up may occur due to inadequate obturation. Root canal retreatment with intracanal medication combining Ca(OH)2 and 2% CHX is effective in relieving symptoms, eliminating persistent microorganisms, and preventing recurrent infection. Keywords: flare-up; root canal retreatment; calcium hydroxide; chlorhexidine Abstrak: Flare-up pasca obturasi merupakan komplikasi endodontik yang ditandai dengan nyeri akut akibat respon inflamasi pada jaringan periapikal. Faktor penyebabnya meliputi ekstrusi debris, obturasi yang tidak adekuat, dan toksisitas bahan sealer. Kami melaporkan seorang pasien laki-laki berusia 18 tahun datang dengan keluhan nyeri pada premolar maksila kiri tiga hari setelah dilakukan obturasi saluran akar. Pemeriksaan radiografi dan CBCT menunjukkan obturasi akar palatal tidak mencapai panjang kerja penuh (underfilling). Dilakukan perawatan ulang berupa pembongkaran gutta-percha menggunakan H-file dan orange oil, dilanjutkan preparasi ulang dengan teknik crown-down. Irigasi intraoperatif menggunakan NaOCl 2,5% dan chlorhexidine 2%. Medikasi intrakanal diberikan berupa kombinasi kalsium hidroksida dan chlorhexidine 2%. Setelah satu minggu, pasien bebas gejala, dan dilakukan obturasi ulang dengan teknik kondensasi lateral menggunakan sealer berbasis eugenol. Pada kontrol dua minggu, pasien tetap asimtomatik dan restorasi akhir dilakukan dengan mahkota jaket PFM. Simpulan studi ini ialah flare-up pasca obturasi dapat dipicu oleh obturasi yang tidak adekuat. Retreatment saluran akar dengan kombinasi medikasi intrakanal Ca(OH)2–CHX 2% efektif dalam meredakan gejala, mengeliminasi mikroorganisme persisten, serta mencegah infeksi berulang. Kata kunci: flare-up; perawatan saluran akar ulang; kalsium hidroksida; chlorhexidine